Answer:
b. -1
Step-by-step explanation:
9=4a+13
-13 -13
--------------
-4=4a
4a/-4
a=-1
The answer is c because you need to multiply both numbers inside the parentheses by the number on the outside
We know that
case 1)
Applying the law of sines
a/Sin A=b/Sin B
A=56°
a=12
b=14
so
a*Sin B=b*Sin A----> Sin B=b*Sin A/a---> Sin B=14*Sin 56°/12
Sin B=0.9672
B=arc sin (0.9672)------> B=75.29°-----> B=75.3°
find angle C
A+B+C=180°-----> C=180-(A+B)----> C=180-(56+75.3)----> C=48.7°
find c
a/Sin A=c/Sin C----> c=a*Sin C/Sin A----> c=12*Sin 48.7°/Sin 56°)
c=10.87-----> c=10.9
the answer Part 1)
the dimensions of the triangle N 1
are
a=12 A=56°
b=14 B=75.3°
c=10.9 C=48.7°
case 2)
A=56°
a=12
b=14
B=180-75.3----> B=104.7°
find angle C
A+B+C=180°-----> C=180-(A+B)----> C=180-(56+104.7)----> C=19.3°
find c
a/Sin A=c/Sin C----> c=a*Sin C/Sin A----> c=12*Sin 19.3°/Sin 56°)
c=4.78-----> c=4.8
the answer Part 2)
the dimensions of the triangle N 2
are
a=12 A=56°
b=14 B=104.7°
c=4.8 C=19.3°
The length of the line joining the center of the circle and each coordinate is equal.
Let the center of the circle be (a, b), then
(a - 10)^2 + (b - 3)^2 = (a - 3)^2 + (b - 10)^2 = (a + 4)^2 + (b - 3)^2
a^2 - 20a + 100 + b^2 - 6b + 9 = a^2 - 6a + 9 + b^2 - 20b + 100 = a^2 + 8a + 16 + b^2 - 6b + 9
a^2 - 20a + 100 + b^2 - 6b + 9 = a^2 - 6a + 9 + b^2 - 20b + 100 . . . (1)
a^2 - 20a + 100 + b^2 - 6b + 9 = a^2 + 8a + 16 + b^2 - 6b + 9 . . . (2)
From (1): 14a - 14b = 0 => a = b
From (2): 28a = 84 => a = 84/28 = 3
Therefore, center = (a, b) = (3, 3)
Answer:
83! :)
Step-by-step explanation:
It all equals 180.
So,
53+44+?=180
180-53-44=83! :)
83+53+44=180! :)